ANOMALI MEDAN GRAVITASI UNTUK IDENTIFIKASI PATAHAN DAERAH MANIFESTASI PANAS BUMI DI SEKITAR GUNUNG TAMPUSU - Herry Manik; Cyrke A. N. Bujung; Jeane Tumangkeng (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Geothermal manifestation area around Tampusu Mountain is an area surrounded by highlands and lowlands. The existence of the highlands and lowlands allows the fault in the Geothermal Manifestation area around Mount Tampusu. The purpose of this study was to determine the presence of faults in the geothermal manifestation area around Tampusu Mountain based on the Gravity Method. From the results of the study, high bouguer anomaly values ​​are located in the southeast of Tampusu Mountain, with a distribution value of 152.4 - 164.4 mGal (0,001524 – 0,001644 m/s2). Whereas for areas with low bouguer anomaly values are in the southwestern part of Mount Tampusu with values ​​126 - 136 mGal (0,00126 – 0,00136 m/s2). This anomaly variation is probably caused by differences in the density of rocks scattered in the Geothermal Manifestation Area around Tampusu Mountain. Through Bouger Anomaly Value Mapping, it is estimated that the fault in the Geothermal Manifestation area around Mount Tampusu is in the southeastern part of Mount Tampusu which leads to the Northeast, based on the drastic increase in the value of the bouguer anomaly. Fault that is in the Geothermal Manifestation area around Mount Tampusu is classified as a normal fault or fault down.